HIV-1 Drug Resistance Mutations and Their Clinical Implications in South Korea - Yun, Jiwon; Jung, Kiwook; Park, Jae Hyeon; Bang, Ji Hwan; Kim, Namhee; Roh, Eun Youn; Shin, Sue; Yoon, Jong Hyun; Park, Hyunwoong (Laboratory Medicine Online, 2022)
Background: While the incidence of new human immunodeficiency virus (HIV) infections has decreased, the dramatic rise in antiretroviral therapy (ART) use will likely increase the prevalence of drug resistance mutations (DRMs). This study aimed to investigate the prevalence and profile of HIV-1 DRMs in ART-naïve and ART-experienced patients in South Korea and determine the correlation between the degree of DRM and the clinical response. Methods: Thirty-six ART-naïve and 8 ART-experienced HIV-1–infected Korean patients referred for standard genotypic resistance testing (SGRT) between 2018 and 2019 were enrolled. Their SGRT results, viral loads, and CD4+ T cell counts were analyzed. Results: Protease inhibitor (PI)-related DRMs were the most frequently observed mutations in ART-naïve (52.8%) and ART-experienced (50.0%) groups, followed by nonnucleoside reverse transcriptase inhibitor (NNRTI)-related and integrase inhibitor (INSTI)-related DRMs. Major DRMs were observed only as NNRTI-related DRMs. The prevalence of transmitted drug resistance (TDR) was 55.6%, which was markedly higher than that previously reported. The changes in viral loads and CD4 counts in ART-naïve patients showed no correlation with the degree of DRM (major, minor, and none). All ART-naïve patients were treated with INSTI-based regimens, and most showed very good responses. Conclusions: The distribution of HIV-1 DRMs in Korean patients was biased toward PI-related and minor DRMs, and DRM severity was not associated with the clinical response. This study provides valuable information on the recent DRM profile among Korean HIV-1 patients and emphasizes the importance of drug resistance genotyping. KCI Citation Count: 0